2015
DOI: 10.1007/s00268-015-3083-8
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Prediction of Lymph Node Status by Circulating Mir‐18b and Mir‐20a During Chemoradiotherapy in Patients with Rectal Cancer

Abstract: MicroRNA expression in patient plasma changes during preoperative CRT. The alteration is not continuous and the meaning requires additional analysis on a larger patient cohort. The co-occurrence of reduced miR-18b and miR-20a expression with lymph node negativity after preoperative CRT could help to stratify the surgical procedure with respect to total mesorectal excision and LR if validated prospectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…miR-20a is a member of the miR-17-92 cluster (including miR-17, miR-18a, miR-19a, miR-20a, miR-19b-1 and miR-92a-1), which is commonly upregulated in malignant cancer and involved in carcinogenesis as the classical oncogene (16). Previous studies have reported upregulated expression levels of circulating miR-20a in malignant neoplasms, such as non-small cell lung cancer (NSCLC), and in cervical, hepatoma, colorectal and prostate cancers (17)(18)(19)(20)(21)(22). However, the association between the expression level of miR-20a and GC is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…miR-20a is a member of the miR-17-92 cluster (including miR-17, miR-18a, miR-19a, miR-20a, miR-19b-1 and miR-92a-1), which is commonly upregulated in malignant cancer and involved in carcinogenesis as the classical oncogene (16). Previous studies have reported upregulated expression levels of circulating miR-20a in malignant neoplasms, such as non-small cell lung cancer (NSCLC), and in cervical, hepatoma, colorectal and prostate cancers (17)(18)(19)(20)(21)(22). However, the association between the expression level of miR-20a and GC is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of miR-17-92 in tumors has a correlation with a higher risk of tumor relapse. Azizian et al [94] also found that downregulated miR-18a and miR-20a in plasma were associated with negative lymph nodes after surgery. However, a study from the Czech Republic showed that miR-17-3p and miR-92a in serum had no significant differences between colorectal cancer and health controls [95].…”
Section: Colorectal Cancermentioning
confidence: 94%
“…Preoperative CRT blood circulating miR-20a can be used as a marker to indicate lymph node status of patients with locally advanced rectal cancer following neoadjuvant CRT. Additionally, the differential regulation of miR-20a before and after radiotherapy and chemotherapy, in patients with rectal cancer, may be used as a marker for monitoring tumor response before and after radiotherapy and chemotherapy (113)(114)(115).…”
Section: Mir-20a May Be Used As a Monitoring Indicator During Chemothmentioning
confidence: 99%
“…Chemotherapy is a widely used treatment in patients with CRC, however resistance can occur and the mechanisms behind this are undetermined. miR-20a has been indicated to be an effective indicator in monitoring response to treatment (112)(113)(114)(115)121). Furthermore, carcinoembryonic antigen (CEA) is a common tumor marker in gastrointestinal cancer, but its specificity and sensitivity are low.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%